A Case of MuSK Myasthenia Gravis Presenting With Persistent Respiratory Insufficiency. Issue 1 (September 2021) - Tsai, Carolyn; Howard, James F.; Mehrabyan, Anahit
Abstract : Abstract: Muscle-specific kinase (MuSK) antibody is seen in 4%–10% of patients with myasthenia gravis (MG), with 40% of these patients reporting bulbar weakness as the initial symptom. We present the case of a 40-year-old woman with MuSK MG whose only presenting symptom was progressive respiratory insufficiency necessitating BiPAP use 16–24 hours daily. She was unresponsive to treatment for cardiac and pulmonary causes and thus referred to neurology. Initial workup directed toward autoimmune and genetic myopathies was unrevealing. MuSK antibodies were positive (60.7 nmol/L, nl 0.00–0.02). Electrodiagnostic studies were unremarkable other than single fiber electromyography which was consistent with a defect in neuromuscular transmission. Treatment with prednisone, plasma exchange, and rituximab led to improvement to reliance on BiPAP only at night. However, her most treatment refractory and quality of life limiting symptom continues to be respiratory insufficiency. Further investigation to better characterize differential response to treatment in this subset of patients with MuSK MG may be needed.